CLINICAL FINDINGS OF EYES WITH MACULAR EDEMA ASSOCIATED WITH BRANCH RETINAL VEIN OCCLUSION REFRACTORY TO RANIBIZUMAB. Issue 7 (July 2018) - Hasegawa, Taiji; Kawano, Taizo; Maruko, Ichiro; Koizumi, Hideki; Iida, Tomohiro
Abstract : Purpose: To determine the relationship between the clinical findings and the response to ranibizumab therapy in eyes with macular edema associated with branch retinal vein occlusion. Methods: We reviewed the medical records of 68 patients with macular edema associated with a branch retinal vein occlusion. The patients were placed in the refractory group if the central foveal thickness remained more than 250 μ m throughout the 6-month study period despite the ranibizumab therapy; otherwise, they were placed in the responsive group. Results: Sixty (88.2%) of 68 eyes were placed in the responsive group and the other 8 eyes (11.8%) were placed in the refractory group. At the pretreatment examination, fluorescein angiography showed extensive leakage from occluded vessels in 52 (86.7%) of the 60 eyes in the responsive group and focal leakages from microaneurysms or dilated capillaries in the other 8 eyes (13.3%). In the refractory group, 7 (87.5%) of 8 eyes had only focal leakage and 1 eye (12.5%) had extensive leakage ( P < 0.0001). The mean initial subfoveal choroidal thickness in the eyes with branch retinal vein occlusion in the responsive group was significantly thicker than that in the fellow eyes (278.0 ± 90.5 μ m, 249.9 ± 94.4 μ m; P < 0.0001). On the other hand, the mean initial subfoveal choroidal thickness in the refractory group was not significantly different from that of the fellow eyes ( P = 0.4002). Conclusion: The dye leakage pattern in the fluorescein angiography images and choroidal thickness may be associated with response to ranibizumab therapy. Abstract : Eyes with only focal leakages from microaneurysms or dilated capillaries in the fluorescein angiographic images tend to resist an intravitreal ranibizumab injection for macular edema associated with a branch retinal vein occlusion.